Metal phosphide electrocatalyst as well as preparation method and application thereof
The preparation of metal phosphide nanoparticles such as Fe2P, Co2P and FeCo through soybean raw materials, combined with nitrogen and carbon doping to form a catalyst with core-shell structure, solving the problems of high cost and complex process of precious metal catalysts, and achieving efficient and stable OER/ ORR catalytic effect, suitable for clean energy devices.
Patent Information
- Application Number
- CN202311103063.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2024-12-24
AI Technical Summary
The existing precious metal-based catalysts are slow and costly in oxygen reduction reactions, hydrogen evolution reactions and oxygen evolution reactions, which limits their application in clean energy devices. The preparation process of non-precious metal phosphide catalysts is complex and has low efficiency, so they cannot be simultaneously It has dual functions of OER/ORR.
Using soybeans as raw materials, metal phosphide nanoparticles such as Fe2P, Co2P and FeCo are prepared by thermal decomposition method of tofu gel. Combined with nitrogen and carbon doping, metal phosphide electrocatalysts formed by core-shell structure and three-dimensional porous network, using soybeans The nitrogen, phosphorus and carbon elements in it achieve low-cost and efficient catalyst preparation.
The prepared metal phosphide electrocatalysts exhibit high catalytic activity and stability in alkaline electrolytes, which are better than RuO2 and Pt-based commercial catalysts, overcome the high cost and process complexity of precious metal catalysts, and have the characteristics of green and environmental protection. .
Smart Images

Figure CN119181814A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel catalytic materials and relates to a metal phosphide electrocatalyst and a preparation method and application thereof. Background Art
[0002] The rapid growth of global energy demand and climate change have brought major challenges to the development of clean and sustainable energy. For example, the oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), and oxygen evolution reaction (OER) involved in fuel cells, zinc-air batteries, and water electrolysis are considered to be fundamental issues in the development of clean energy devices, but their slow kinetics require the use of efficient catalysts to reduce the high overpotential. Currently, commercial OER, HER, and ORR catalysts are mainly based on Ir / Ru-based and Pt-based materials.
[0003] However, these precious metal-based catalysts have high costs and do not meet the requirements of low cost or abundant resources, which greatly limits their application in energy devices. Non-precious metal electrocatalysts are increasingly favored due to their advantages such as cheapness, cleanliness, and sustainability. The development of cheap non-precious metal electrocatalysts is crucial to solving the problems related to the rapid growth of global energy demand. For example, Ni, Fe, Mn, V, Co and their oxides, carbides, phosphides, nitrides, etc. have made great progress. Carbon-coated transition metal catalysts or combining carbon matrices with transition metal materials have been used as an effective strategy to improve catalytic performance. In the past few decades, transition metal-nitrogen / carbon catalysts (MN / C) have shown great potential in the field of electrocatalysis. However, metal phosphides are currently mainly prepared by high-temperature annealing using phosphorus-containing organic matter. The most commonly used nitrogen and phosphorus sources are expensive or even toxic, and have low efficiency and complex processes. They cannot have both OER / ORR dual functions, and their application in fuel cells is very limited. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a green, environmentally friendly, low-cost, scalable metal phosphide electrocatalyst with high activity and high stability.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A metal phosphide electrocatalyst comprises metal nanoparticles and phosphorus and nitrogen co-doped carbon, wherein the metal nanoparticles include Fe2P, Co2P, FeCo and Fe-PO4.
[0007] Preferably, the doping forms of nitrogen mainly include pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and oxidized nitrogen.
[0008] In the above-mentioned metal phosphide electrocatalyst, the catalyst has a core-shell structure of carbon-coated metal nanoparticles and a three-dimensional porous network structure, and the specific surface area of the catalyst is 5-450m 2 g -1 , pore size is 5-90nm.
[0009] Preferably, the particle size of the metal nanoparticles is 5-20 nm.
[0010] The present invention also provides a method for preparing the above metal phosphide electrocatalyst, the method comprising the following steps:
[0011] S1, preparing soybean milk from soybeans, mixing with cobalt salt and iron salt to obtain iron-cobalt tofu gel;
[0012] S2, the iron-cobalt tofu gel is compressed and freeze-dried to obtain an aerogel;
[0013] S3. The aerogel is heat-treated in a protective atmosphere, then immersed in a sulfuric acid solution, and finally washed and dried to obtain a catalyst.
[0014] The present invention uses soybean as raw material. In addition to the abundant N and C in the protein molecules, soybean also provides a large amount of P. For example, phytic acid in soybean can be used as a natural phosphorus agent and has a dual effect, that is, it is simultaneously incorporated into carbon to neutralize and generate metal phosphides. Using soybean as a precursor, the synthesis of iron / cobalt phosphide and N, P-doped carbon (NPC) mixed catalyst includes the preparation of iron / cobalt cross-linked tofu gel (Fe / Co-tofu) and subsequent thermal decomposition. First, the beans are crushed and uniformly emulsified in a soymilk machine, in which the hydrogen bonds and disulfide bonds in the soy protein are destroyed, thereby becoming negatively charged, and then the Fe 3+ and Co 2+ The cations can be uniformly adsorbed on the soy protein molecules, and then heated to cause further cross-linking reactions, which enhance the hydrophobic interaction between the protein molecules and form a stable and strong gel network. The precipitated protein is plasticized and freeze-dried to present an aerogel with a three-dimensional porous structure. The subsequent heat treatment simultaneously reduces / phosphorylates the iron / cobalt cations, carbonizes the soy protein, and in-situ atomic N, P doping, obtaining a metal phosphide / NPC mixture at one time, which inherits the highly porous structure of tofu hydrogel.
[0015] In the above-mentioned method for preparing a metal phosphide electrocatalyst, in step S1, the temperature during the process of making soybean milk from soybeans is 20-50° C., the slurry ratio is 1:4-1:9, and the rotation speed is 500-800 rpm.
[0016] Preferably, the soybeans are first soaked for 8-15 hours, then crushed, filtered through a 80-240 mesh filter, and then made into soy milk with a slurry ratio of 1:4 to 1:9 at 20-50° C. and 500-800 rpm.
[0017] In the above-mentioned method for preparing a metal phosphide electrocatalyst, the cobalt salt in step S1 is at least one of Co(NO3)2·6H2O and CoCl2·6H2O.
[0018] In the above-mentioned method for preparing a metal phosphide electrocatalyst, the iron salt in step S1 is at least one of Fe(NO3)3·9H2O and FeCl3·6H2O.
[0019] In the above method for preparing a metal phosphide electrocatalyst, the molar ratio of the cobalt salt to the iron salt in step S1 is 1-3:1.
[0020] In the above-mentioned method for preparing a metal phosphide electrocatalyst, in step S2, the iron-cobalt tofu gel needs to be heated to 70-95° C. before pressing, and then allowed to stand for 10-30 minutes.
[0021] In the above-mentioned method for preparing a metal phosphide electrocatalyst, the heat treatment temperature in step S3 is to keep the temperature at 400-500° C. for 1-3 hours, and then keep the temperature at 600-1000° C. for 1.5-2.5 hours.
[0022] Preferably, the protective atmosphere is one of ammonia and nitrogen.
[0023] More preferably, the protective atmosphere is ammonia.
[0024] More preferably, the flow rate of the protective atmosphere is 50-300 ml / min.
[0025] In the above-mentioned method for preparing a metal phosphide electrocatalyst, the sulfuric acid concentration in step S3 is 0.2-1 mol / L, and the soaking time is 3-30 h.
[0026] Preferably, the metal phosphide electrocatalyst comprises Fe, Co, P, N, O and C elements, wherein the atomic percentage of each element is: 2.0-3.0% Fe, 3.0-3.5% Co, 3.5-4.0% P, 1.0-1.5% N, 1.5-2.0% O and 85.0-89.0% C.
[0027] The present invention also provides a battery, comprising the above-mentioned metal phosphide electrocatalyst.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The metal phosphide electrocatalyst prepared by the present invention has high catalytic activity and stability. Its catalytic activity in alkaline electrolyte is higher than that of RuO2 and 20wt.% Pt / C commercial catalysts. The zinc-air battery and full water splitting test data prepared by the present invention are better than those of commercial precious metal catalysts. It has the prospect of replacing traditional RuO2 and Pt-based precious metal catalysts, and overcomes the shortcomings of commercial precious metal catalysts such as complex production process, high price and poor stability.
[0030] 2. The metal phosphide electrocatalyst of the present invention uses biomass soybeans as raw materials. Soybeans are rich in nitrogen, phosphorus, carbon and other elements, and are green, low-cost and high-utilization.
[0031] 3. The metal phosphide electrocatalyst of the present invention utilizes phosphorus, which is rich in soybeans, to achieve the self-phosphorization effect of the metal, thus overcoming the shortcomings of the existing non-precious metal phosphide catalyst preparation process, such as the need to add toxic phosphorus sources.
[0032] 4. The metal phosphide electrocatalyst of the present invention is inspired by the traditional Chinese tofu preparation process. During the tofu preparation process, the magnesium chloride in the brine is replaced with a strong electrolyte such as nitrate to achieve large-scale preparation of the catalyst, thus overcoming the complex preparation process of existing non-precious metal catalysts.
[0033] 5. The metal phosphide electrocatalyst of the present invention has a core-shell structure, which effectively prevents the corrosion of metal nanoparticles; during pyrolysis and freeze-drying, the evaporation of water in the iron-cobalt tofu gel makes the catalyst have a porous structure, which effectively improves the catalyst performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The XRD patterns of the composite electrocatalysts prepared in Examples 1-4;
[0035] Figure 2 TEM image of the Fe2P / Co2P / FeCo@NPC composite electrocatalyst prepared in Example 1.
[0036] Figure 3 This is the XPS spectrum of the C element in the Fe2P / Co2P / FeCo@NPC composite electrocatalyst prepared in Example 1;
[0037] Figure 4 This is the XPS spectrum of the N element in the Fe2P / Co2P / FeCo@NPC composite electrocatalyst prepared in Example 1;
[0038] Figure 5 The XPS spectrum of the P element in the Fe2P / Co2P / FeCo@NPC composite electrocatalyst prepared in Example 1;
[0039] Figure 6 Specific surface area diagram of the composite electrocatalyst prepared in Examples 1-4;
[0040] Figure 7 The pore size distribution diagram of the composite electrocatalyst prepared in Example 1-4;
[0041] Figure 8 This is the SEM image of the Fe2P@NPC electrocatalyst prepared in Example 2;
[0042] Fig. 9 This is a SEM image of the Co2P@NPC composite electrocatalyst prepared in Example 3;
[0043] Fig.10 This is a SEM image of the NPC electrocatalyst prepared in Example 4;
[0044] Fig.11 XRD patterns of the composite electrocatalysts prepared in Examples 1, 5, and 6;
[0045] Fig.12 The SEM spectrum of the Fe2P / Co2P / FeCo@NPC-1 composite electrocatalyst prepared in Example 5;
[0046] Fig.13 The specific surface area diagram of the composite electrocatalyst prepared in Examples 1, 5, and 6;
[0047] Fig.14 The pore size distribution diagram of the composite electrocatalyst prepared in Examples 1, 5, and 6;
[0048] Fig.15 The SEM spectrum of the Fe2P / Co2P / FeCo@NPC-1 composite electrocatalyst prepared in Example 6;
[0049] Fig.16 This is a comparison chart of the ORR reaction activities of the composite catalysts prepared in Examples 1-4 and the 20 wt.% Pt / C catalyst in Comparative Example 1 in 0.1 M KOH solution.
[0050] Fig.17 This is a comparison chart of the ORR reaction stability of the composite catalysts prepared in Examples 1-4 and the 20 wt.% Pt / C catalyst in Comparative Example 1 in 0.1 M KOH solution.
[0051] Fig.18 This is a comparison chart of the OER reaction activities of the composite catalysts prepared in Examples 1-4 and the RuO2 catalyst in Comparative Example 1 in 1M KOH solution.
[0052] Fig.19This is a comparison chart of the HER reaction activities of the composite catalysts prepared in Examples 1-4 and the 20 wt.% Pt / C catalyst in Comparative Example 1 in 0.1 M KOH solution.
[0053] Fig. 20 This is a comparison chart of the cyclic charge and discharge of a zinc-air battery assembled using the composite catalyst prepared in Examples 1-4 and the 20 wt.% Pt / C-RuO2 catalyst in Comparative Example 1 as air electrodes. DETAILED DESCRIPTION
[0054] In order to make those skilled in the art better understand the technical scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. These embodiments are exemplary, and the disclosure of the present invention is not limited thereto, and the accompanying drawings used herein are only for better illustrating the disclosure of the present invention, and do not have a limiting effect on the scope of protection. If there is no special explanation, the raw materials used in the following specific examples of the present invention are all raw materials commonly used in this area, and the methods used in the embodiments are all conventional methods in this area.
[0055] Embodiment 1:
[0056] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and the subsequent treatment was carried out at 25 ° C for 40 minutes. Then, after filtering through a 120-mesh gauze, uniform soybean milk was obtained. After that, 0.02 mol of Fe(NO3)3·9H2O and 0.03 mol of Co(NO3)2·6H2O were evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an NH3 atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for 24 hours, then washed with deionized water and dried to obtain a Fe2P / Co2P / FeCo@NPC composite electrocatalyst.
[0057] from Figure 1 It can be seen that the presence of Fe2P, Co2P and FeCo nanoparticles in the carbon matrix was observed, confirming that the catalyst is composed of an amorphous carbon composite doped with FeCo, Co2P, Fe2P and nitrogen and phosphorus.
[0058] from Figure 2It can be seen that the metal nanoparticles are evenly distributed in the carbon matrix with a diameter of 5-20nm, and the FeCo alloy nanoparticles are tightly wrapped by graphite. The percentages of each element in the catalyst are 2.84%, 3.17%, 3.76%, 1.07%, 1.83% and 87.67%.
[0059] from Figure 3 It can be seen that CP, CC, CN and CO are displayed, reflecting the successful incorporation of N and P atoms into the carbon substrate.
[0060] from Figure 4 It can be seen that the doped N types include pyridinic-N, pyrrolic-N, graphitic-N and oxidized-N, which increase the defect degree of the carbon substrate and improve the catalyst performance.
[0061] from Figure 5 It can be seen that the coexistence of metal phosphides (P-Fe, P-Co), P-doped carbon (P-C1, P-C3) and Fe-PO4 was confirmed.
[0062] from Figure 6 and Figure 7 It can be seen that the specific surface area of the composite catalyst is between 5-450m 2 g -1 The pore size is between 5-90nm.
[0063] Embodiment 2:
[0064] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through 120 mesh gauze, uniform soybean milk was obtained. After that, 0.02 mol of Fe(NO3)3·9H2O was evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an NH3 atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for 24 hours, then washed with deionized water and dried to obtain a Fe2P@NPC composite electrocatalyst.
[0065] from Figure 1 It can be seen that the presence of Fe2P nanoparticles in the carbon matrix was observed, confirming that the catalyst was composed of an amorphous carbon composite co-doped with Fe2P and nitrogen and phosphorus.
[0066] from Figure 8 It can be seen that the metal nanoparticles are evenly distributed in the carbon matrix with a diameter of 5-20nm.
[0067] from Figure 6 and Figure 7 It can be seen that the specific surface area of the prepared catalyst is between 5-450m 2 g -1 The pore size is between 5-90nm.
[0068] Embodiment 3:
[0069] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through a 120-mesh gauze, uniform soybean milk was obtained. After that, 0.03 mol of Co(NO3)2·6H2O was evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an NH3 atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for 24 hours, then washed with deionized water and dried to obtain the Co2P@NPC composite electrocatalyst.
[0070] from Figure 1 It can be seen that the presence of Co2P nanoparticles in the carbon matrix confirms that the catalyst is composed of an amorphous carbon complex co-doped with Co2P and nitrogen and phosphorus;
[0071] from Fig. 9 It can be seen that the metal nanoparticles are evenly distributed in the carbon matrix with a diameter of 5-20nm;
[0072] from Figure 6 and Figure 7 It can be seen that the specific surface area of the catalyst is between 5-450m 2 g -1 The pore size is between 5-90nm.
[0073] Embodiment 4:
[0074] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, uniform soybean milk was obtained by filtering through 120 mesh gauze. After that, 0.05 mol of gluconolactone was evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an NH3 atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for 24 hours, then washed with deionized water and dried to obtain an NPC composite electrocatalyst.
[0075] from Figure 1 It can be seen that the presence of amorphous carbon was observed, confirming that the catalyst was composed of amorphous carbon complex co-doped with nitrogen and phosphorus.
[0076] from Fig.10 It can be seen that the prepared NPC electrocatalyst is in block form with a length of 5-50 microns.
[0077] from Figure 6 and Figure 7 It can be seen that the specific surface area of the catalyst is between 5-450m 2 g -1 The pore size is between 5-90nm.
[0078] Embodiment 5:
[0079] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through 120 mesh gauze, uniform soybean milk was obtained. After that, 0.005 mol of Fe(NO3)3·9H2O and 0.0075 mol of Co(NO3)2·6H2O were evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold, pressed for 30 minutes, and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an NH3 atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5 M H2SO4 for 24 h, then washed with deionized water and dried to obtain the Fe2P / Co2P / FeCo@NPC-1 composite electrocatalyst.
[0080] Embodiment 6:
[0081] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through a 120-mesh gauze, uniform soybean milk was obtained. After that, 0.03 mol of Fe(NO3)3·9H2O and 0.045 mol of Co(NO3)2·6H2O were evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an NH3 atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for 24 hours, then washed with deionized water and dried to obtain a Fe2P / Co2P / FeCo@NPC-3 composite electrocatalyst.
[0082] Embodiment 7:
[0083] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through a 120-mesh gauze, uniform soybean milk was obtained. After that, 0.02 mol of Fe(NO3)3·9H2O and 0.03 mol of Co(NO3)2·6H2O were evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an Ar atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 700 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for 24 hours, then washed with deionized water and dried to obtain the Fe2P / Co2P / FeCo@NPC-A700 composite electrocatalyst.
[0084] Embodiment 8:
[0085] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through a 120-mesh gauze, uniform soybean milk was obtained. After that, 0.02 mol of Fe(NO3)3·9H2O and 0.03 mol of Co(NO3)2·6H2O were evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an Ar atmosphere, first heated to 450 ° C, kept warm for 1 hour, and then heated to 600 ° C and kept warm for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for one day, then washed with deionized water and dried to obtain the Fe2P / Co2P / FeCo@NPC-A800 composite electrocatalyst.
[0086] Embodiment 9:
[0087] 50 grams of soybeans were soaked in distilled water at room temperature for 10 hours, and then the fully expanded beans were put into a soybean milk machine, 400 ml of distilled water was added, and subsequent treatment was carried out at 25 ° C for 40 minutes. Next, after filtering through 120 mesh gauze, uniform soybean milk was obtained. After that, 0.02 mol of Fe(NO3)3·9H2O and 0.03 mol of Co(NO3)2·6H2O were evenly dispersed in 400 mL of the above filtrate and stirred at room temperature for 2 hours. The mixture was then heated to 90 ° C and allowed to stand for 10 minutes, then poured into a mold and pressed for 30 minutes and then placed in a freeze dryer to dry to obtain aerogel. The aerogel was pyrolyzed in an Ar atmosphere, first heated to 450 ° C for 1 hour, and then heated to 800 ° C for 2 hours. The collected black solid was soaked in 0.5M H2SO4 for one day, then washed with deionized water and dried to obtain the Fe2P / Co2P / FeCo@NPC-A900 composite electrocatalyst.
[0088] Comparative Example 1:
[0089] Conventional commercial 20wt.% Pt / C and RuO2 catalyst (JM Company).
[0090] Fig.16 The ORR reaction activity comparison diagram of the composite catalyst prepared in Examples 1-4 and the 20wt.% Pt / C catalyst in Comparative Example 1 in 0.1M KOH solution. The onset potential (Eon) and half-wave potential (Eon) of FeCo / Co2P / Fe2P@NPC are shown in Table 1. 1 / 2) are 0.88 and 0.79 V, respectively, which are on par with Pt / C (0.91 and 0.80 V), and exceed Fe2P@NPC (0.84 and 0.78 V, respectively), Co2P@NPC (0.80 and 0.65 V, respectively), NPC (0.80 and 0.62 V, respectively), and biomass-derived Fe / Co-C catalysts reported in the literature. The metal-free NPC has the worst activity, and Fe2P on and E 1 / 2 All of them are superior to the Co2P electrode, and Fe2P makes a dominant contribution to the ORR on the FeCo / Co2P / Fe2P@NPC electrode.
[0091] Fig.17 Comparison of the ORR reaction stability of the composite catalysts prepared in Examples 1-4 and the 20wt.% Pt / C catalyst in Comparative Example 1 in 0.1M KOH solution. The current of FeCo / Co2P / Fe2P@NPC, Fe2P@NPC and Co2P@NPC electrodes decreased slightly by 3%, 6% and 7%, respectively. In contrast, under the same test conditions, the current retention rates of NPC and Pt / C electrodes decreased significantly by 61.7% and 64.5%, respectively.
[0092] Fig.18 The OER activity comparison of the composite catalysts prepared in Examples 1-4 and the RuO2 catalyst in Comparative Example 1 in 1M KOH solution. The FeCo / Co2P / Fe2P@NPC electrode has the highest OER activity. It is worth noting that it can provide 10mA cm at a low overpotential of 281mV. -2 The current density is better than that of RuO2, Fe2P@NPC, Co2P@NPC and NPC
[0093] Fig.19 The HER reaction activity comparison chart of the composite catalyst prepared in Examples 1-4 and the 20wt.% Pt / C catalyst in Comparative Example 1 in 0.1M KOH solution. It can be seen that the high activity of FeCo / Co2P / Fe2P@NPC is lower than that of precious metal Pt / C, but its Tafel slope is higher than that of precious metal Pt / C.
[0094] Fig. 20The cyclic charge-discharge comparison diagram of the zinc-air battery assembled with the composite catalyst prepared in Examples 1-4 and the 20wt.% Pt / C-RuO2 catalyst in Comparative Example 1 as the air electrode. In the long-term discharge-charge cycle, the ZAB based on FeCo / Co2P / Fe2P@NPC maintained the original charge-discharge voltage difference well after 720h of continuous operation. It increased from an initial value of 0.89V to a final value of 0.90V. In contrast, the performance of zinc-air batteries based on air catalysts such as PtC-RuO2, Fe2P@NPC, Co2P@NPC and NPC decreased more significantly, as shown by a larger increase in the voltage gap within a shorter test period, reflecting the superior ORR / OER biocatalytic stability and structural toughness of Fe2P / Co2P / FeCo@NPC catalysts over commercial precious metal catalysts.
[0095] The present invention also studies the effect of the loading amount of iron / cobalt salt in the precursor gel on the structural evolution and catalytic performance of the material through Examples 5 and 6. ICP analysis shows that the increase of metal salt in the precursor does bring about an increase in the content of Fe and Co in the product. It is worth noting that XRD shows that there is no FeCo alloy in the sample FeCo / Co2P / Fe2P@NPC-1, while FeCo / Co2P / Fe2P@NPC-3 has the same crystalline phase as FeCo / Co2P / Fe2P@NPC. This indicates that at a lower amount of metal salt added, the P species released by the pyrolysis of phytic acid in soybeans is sufficient to form Fe / Co phosphide, and as the amount of metal salt added increases, the excess part will be reduced to a metal form, i.e., FeCo alloy. SEM images show aggregated particles generated in the carbon matrix of FeCo / Co2P / Fe2P@NPC-3, which coincides with its decrease in specific surface area. By comparing the LSV curves and Tafel slopes, it is found that the FeCo / Co2P / Fe2P@NPC electrode has the best ORR, OER and HER activities. In contrast, the electrochemical performance of the sample with the highest metal loading (i.e., FeCo / Co2P / Fe2P@NPC-3) decreased, which may be due to the severe aggregation of metal nanoparticles and the reduction of active surface area. This further proves that the combination of higher dispersion and high loading of metal active species in a highly conductive carbon matrix is the key to increase the catalytic activity of the hybrid material.
[0096] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0097] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0098] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A metal phosphide electrocatalyst, characterized in that The catalyst comprises metal nanoparticles and phosphorus and nitrogen co-doped carbon, wherein the metal nanoparticles include Fe2P, Co2P, FeCo and Fe-PO4.
2. A metal phosphide electrocatalyst according to claim 1, characterized in that: The catalyst has a core-shell structure of carbon-coated metal nanoparticles and a three-dimensional porous network structure. The specific surface area of the catalyst is 5-450m 2 g -1 , pore size is 5-90nm.
3. A method for preparing the metal phosphide electrocatalyst according to claim 1, characterized in that: The method comprises the following steps: S1, preparing soybean milk from soybeans, mixing with cobalt salt and iron salt to obtain iron-cobalt tofu gel; S2, the iron-cobalt tofu gel is compressed and freeze-dried to obtain an aerogel; S3. The aerogel is heat-treated in a protective atmosphere, then immersed in a sulfuric acid solution, and finally washed and dried to obtain a catalyst.
4. The method for preparing a metal phosphide electrocatalyst according to claim 3, characterized in that: In step S1, the temperature of soybeans during the process of making soy milk is 20-50° C., the pulp ratio is 1:4-1:9, and the rotation speed is 500-800 rpm.
5. The method for preparing a metal phosphide electrocatalyst according to claim 3, characterized in that: In step S1, the cobalt salt is at least one of Co(NO3)2·6H2O and CoCl2·6H2O.
6. The method for preparing a metal phosphide electrocatalyst according to claim 3, characterized in that: In step S1, the iron salt is at least one of Fe(NO3)3·9H2O and FeCl3·6H2O.
7. The method for preparing a metal phosphide electrocatalyst according to claim 3, characterized in that: In step S1, the molar ratio of the cobalt salt to the iron salt is 1-3:
1.
8. The method for preparing a metal phosphide electrocatalyst according to claim 3, characterized in that: Step S2: The iron-cobalt tofu gel needs to be heated to 70-95° C. before pressing, and then allowed to stand for 10-30 minutes.
9. The method for preparing a metal phosphide electrocatalyst according to claim 3, characterized in that: The heat treatment temperature in step S3 is 400-500°C for 1-3 hours, and then 600-1000°C for 1.5-2.5 hours.
10. A battery, characterized in that: The invention comprises the metal phosphide electrocatalyst according to any one of claims 1 to 2.
